1988
DOI: 10.1021/bi00417a048
|View full text |Cite
|
Sign up to set email alerts
|

Use of site-directed mutagenesis to investigate the basis for the specificity of hirudin

Abstract: Regions of hirudin important for its inhibitory activity with thrombin have been examined by site-directed mutagenesis. Since thrombin has a primary specificity for basic amino acids, each of the three basic residues and the histidine in hirudin were mutated to glutamine. Mutation of Lys-47 caused a small increase (9-fold) in the dissociation constant whereas the other mutations were without effect. These results indicate that hirudin is different from most other inhibitors of serine proteases in that interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
187
1
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(198 citation statements)
references
References 40 publications
8
187
1
2
Order By: Relevance
“…However, mutation of this residue perturbs the free energy of hirudin binding to the fast form by only 0.4 kcal/mol. This finding is in agreement with mutagenesis studies of hirudin that have reported only a modest perturbation of hirudin affinity for the H51Q mutant (20). As to D221 and D222, these residues make no direct contacts with hirudin and therefore the effect seen upon mutation is indirect and mediated by a perturbation of the slow <--fast equilibrium (7).…”
Section: U [supporting
confidence: 90%
“…However, mutation of this residue perturbs the free energy of hirudin binding to the fast form by only 0.4 kcal/mol. This finding is in agreement with mutagenesis studies of hirudin that have reported only a modest perturbation of hirudin affinity for the H51Q mutant (20). As to D221 and D222, these residues make no direct contacts with hirudin and therefore the effect seen upon mutation is indirect and mediated by a perturbation of the slow <--fast equilibrium (7).…”
Section: U [supporting
confidence: 90%
“…A number of mutants have been made in the C-terminal tail of hirudin to investigate its interactions with thrombin (Braun et al, 1988;Stone et al, 1989;Betz et al, 1991a,b;Yue et al, 1992). These are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structures of thrombin (Bode et al, 1989(Bode et al, , 1992 and its complexes with the polypeptide inhibitor hirudin (Kinemage 1; Griitter et al, 1990;Rydel et al, 1990Rydel et al, , 1991 cleft of thrombin, the C-terminal region binds to a positively charged surface groove called the fibrinogen-recognition exosite. The C-terminal region of recombinant hirudin (rhir) between residues 55 and 65 contains five negatively charged residues, and results from studies using site-directed mutagenesis indicate that each of these negatively charged residues (Asp 55: Glu 57: Glu 58: Glu 61', and Glu 62') contributes to the stabilization of the complex (Braun et al, 1988a;Betz et al, 1991). In addition, the effect of ionic strength on the interaction between thrombin and hirudin suggests that electrostatic interactions with the C-terminal region of hirudin are important for the rate of complex formation and the stability of the complex (Stone et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the effect of ionic strength on the interaction between thrombin and hirudin suggests that electrostatic interactions with the C-terminal region of hirudin are important for the rate of complex formation and the stability of the complex (Stone et al, 1989). However, although protein engineering studies indicate that each of the negatively charged residues in the C-terminal region of hirudin makes about the same contribution to binding energy (Braun et al, 1988a;Stone et al, 1989;Betz et al, 1991), 727 …”
mentioning
confidence: 99%
See 1 more Smart Citation